Dictionary of organizational development - Andres, Tomas Quintin Donato 1942- (Quezon City Giraffe Books, 1998)
This is a dictionary that contains terms related to organizational development, its definitions or meanings and some examples. It is intended for use in organizational development subjects and courses, to bridge the gap between managers and subordinates for organizational development and progress.
This dictionary includes more than 2,000 organizational development terms. Aims to bridge the gap between managers and subordinates for organizational development and progress. It is also intended for use in organizational development subjects and courses.
Keywords: Organizational change -- Dictionaries